Influenza in pregnant women during 3 seasons, between 2013-2016 in Portugal - Conde, Patrícia (2017)
Background: Since the 2009 pandemic, pregnant women (PW) have been assumed has a high risk group for increased morbidity and mortality linked to influenza infection. From 2013 to 2016, the Portuguese Influenza Surveillance Programme integrates an obstetric unit network that reports influenza-like illness (ILI) cases and collects nasopharyngeal samples for influenza surveillance and diagnosis. This study aims to characterize cases of influenza infection in pregnant women during 2013-2016 in Portugal. Methods: Between 2013 and 2016, cases of ILI in PW were compared with ILI in childbearing age women (NPW), between 15 and 44 years. In study period were reported 634 ILI cases (220 ILI in 2013/14, 152 in 2014/15 and 262 in 2015/16) of each 149 in PW. Influenza and other respiratory viruses diagnosis were performed by multiplex RT-PCR. Data regarding symptoms, hospitalization, vaccination and antiviral treatment were recorded. Results: During the overall study period the proportion of influenza confirmed cases were similar in PW and NPW, 51% and 54% respectively. The analysis by (sub)type of influenza virus revealed that A(H1)pdm09 season was detected 1.3 times more frequently in PW than in NPW during 2013/14, situation not so evident during 2015/16 season, with low ILI incidence rates. B/Yamagata viruses were identified in PW in a proportion 1.5 times higher than in NPW (2014/15 season). Influenza A(H3) was detected in higher proportion in NPW, 2 to 4 times higher, in 2013/14 and 2014/15 seasons, respectively, when compared with PW. The other respiratory viruses were found in higher percentage among PW, with a positive rate between 55% and 68% during the 3 seasons. RSV, parainfluenza vírus and human metapneumovirus have a higher prevalence in PW, while human rhinovirus reach the higher percentage among NPW. In 660 women ILI cases that reported vaccination status, vaccine coverage was higher in NPW (6.3%;29/463) compared to PW (4.1%;6/143). Vaccine failures were registered in 45% (13/29) cases in NPW and in 67% in PW (4/6). Information on antiviral treatment was reported in 406 ILI cases. Antivirals were prescribed in 8.6% (28/235) of NPW and in 13.6% (11/81) of PW. Were reported 10 PW with need of hospitalization, 6 of these cases positive for influenza A(H1)pdm09 and 1 positive forrhinovirus. None of hospitalized PW were vaccinated. Conclusions: Study shows that PW must still considered a high risk group for influenza and other respiratory viruses infection. Study highlight that influenza A and B presents a higher frequency of infection in PW compared to NPW that might be associated with increased risk for complications. Reinforcement of vaccination campaign will be a challenge in influenza prevention, nevertheless, influenza vaccination is free and highly recommended in Portugal for PW risk group.